A novel theoretical method for predicting the effects of lighting colour temperature on physiological responses and indoor thermal perception. (October 2021) - Omidvar, Amir; Brambilla, Arianna
Abstract: The neural integration of information from different sensory modalities, known as multisensory integration, is a phenomenon that can affect people's thermal perception. Previous experimental research validated the hue-heat hypothesis as one of the contexts of multisensory integration. The present research introduces the equivalent metabolic rate as a novel parameter to include the hue-heat effects in conventional thermal comfort models. To this aim, an analytical expression was developed for calculating the equivalent metabolic rate according to the correlated colour temperature (CCT) of the ambient light and implemented in both steady and transient thermal comfort models. The modified models were validated against published experimental data. The effects of lighting colour on physiological responses and thermal perception were then investigated for four different CCTs under three different indoor temperatures. The simulated results showed that any deviation from CCT 5000 K evokes thermophysiological responses and alters the people's thermal sensation compared to what is expected by standard thermal comfort models. The maximum and minimum lighting effects were observed at 4000 K and 6500 K CCT, respectively. The results also showed that thermal perception is more sensitive to CCT changes in warm environments. Furthermore, it is predicted that the thermal sensation could be changed up to 0.8 units by changing the lighting colour, while the skin temperature and wettedness could change up to 0.8 °C and 0.14, respectively. This paper demonstrates that the novel equivalent metabolic rate parameter can be successfully used to predict the thermal sensation under varying lighting environments, making a substantial contribution to multisensory integration. Highlights: Analytical study of hue-heat effect as a context in multisensory integration. Introducing the equivalent metabolic rate method to simulating the hue-heat effect. Developing the new PMVCCT model to considering lighting colour effects on comfort. Predicting the impact of lighting colour on human thermophysiological responses.